Menuju Kerangka Integratif Pendidikan Prenatal dalam Al-Qur'an: Penafsiran Quraish Shihab terhadap QS. Āli 'Imrān: 35 - Addin Kholisin; Faridatus Sa’adah; Moh. Sulthan Lingga Rajendra Alfanio Guevara (Jawa Timur: Prodi. Ilmu Al Quran dan Tafsir Fakultas Ushuluddin IAI Tarbiyatut Tholabah, 2026)
Growing evidence from developmental psychology, neuroscience, and prenatal health has highlighted the significance of the prenatal period in shaping human development. Nevertheless, studies on Islamic education continue to focus predominantly on postnatal learning, while the Qur'anic foundations of prenatal education remain underexplored. This study aims to reconstruct the concept of Qur'anic prenatal education through Quraish Shihab's interpretation of QS. Āli 'Imrān:35 in Tafsir al-Misbāḥ. Employing a qualitative library research design, the study applies thematic (mawḍū'ī) exegesis combined with content analysis to examine Shihab's interpretation in dialogue with contemporary scholarship on prenatal psychology, developmental neuroscience, and maternal well-being. The findings identify three interconnected principles that constitute the foundation of Qur'anic prenatal education. First, parental commitment (nadhar) establishes intentional preparation before birth as the ethical basis of educational responsibility. Second, spiritual communication through prayer strengthens maternal emotional resilience and nurtures prenatal attachment between mother and fetus. Third, tawakkul functions as a spiritual coping strategy that promotes maternal psychological well-being, reduces stress, and supports healthy fetal development. Together, these principles demonstrate that prenatal education in the Qur'an is both preventive and formative, integrating spiritual values with psychosocial and biological dimensions of pregnancy. This study contributes to Islamic education by reconstructing a comprehensive framework of Qur'anic prenatal education that bridges classical Qur'anic exegesis with contemporary scientific perspectives, thereby providing a conceptual foundation for Islamic parenting education, prenatal counseling, and faith-based maternal health programs.